On a reconstruction problem for membrane systems - Korczyński, W.; Wawrzoła, G.; Wawrzoła, S. (Видавництво Національного університету "Львівська політехніка", 2004)
The problem of reconstruction of an object from some of their reduct is very important in many areas of life and science. It is one of the well known problems in the theory of partial orders. In the paper we describe and solve this problem in a very special case: the infrastructure of Paun’s systems (called also membrane structures). The main result of the paper is an algorithm of reconstruction of the original membrane structure from two of its reducts.